Digital Volume Correlation for large deformations of soft tissues: Pipeline and proof of concept for the application to breast ex vivo deformations. (December 2022) - Lavigne, T.; Mazier, A.; Perney, A.; Bordas, S.P.A.; Hild, F.; Lengiewicz, J.
Abstract: Being able to reposition tumors from prone imaging to supine surgery stances is key for bypassing current invasive marking used for conservative breast surgery. This study aims to demonstrate the feasibility of using Digital Volume Correlation (DVC) to measure the deformation of a female quarter thorax between two different body positioning when subjected to gravity. A segmented multipart mesh (bones, cartilage and tissue) was constructed and a three-step FE-based DVC procedure with heterogeneous elastic regularization was implemented. With the proposed framework, the large displacement field of a hard/soft breast sample was recovered with low registration residuals and small error between the measured and manually determined deformations of phase interfaces. The present study showed the capacity of FE-based DVC to faithfully capture large deformations of hard/soft tissues. Graphical abstract: Highlights: Three-step DVC pipeline to measure large displacements with only two X-ray scans. Heterogeneous and regularized DVC was carried out to account for hard/soft tissues. Large amplitude displacement field was accurately measured for a breast.